The effects of combined exposure of solvents and noise on auditory function – A systematic review and meta-analysis - Nakhooda, F; Sartorius, B; Govender, SM (AOSIS, 2019)
Background: Chemical substances can negatively affect the auditory system. Chemical substances alone or combined with high-level noise have recently become a major concern as a cause of occupational hearing loss.